Electrical properties of macroporous silicon structures - Karachevtseva, L.A.; Lytvynenko, O.A.; Malovichko, E.A.; Sobolev, V.D.; Stronska, O.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
The dependencies of electron conductivity, concentration and mobility on pore size and concentration were investigated for macroporous silicon structures. The electron conductivity and concentration in two-layer structures of macroporous silicon, and also in a matrix of macroporous layers have a maximum for a macropore volume of V = 0.3-0.4. Thus the electron mobility decreases monotonically. The experimental results were explained by a model based on the existence of electron-enriched regions around pores, with thickness ΔD ≈ 1 mm formed after electrochemical and chemical treatment of the macropore walls.